Early Miocene ventricose bamboo from south Asia with implications for evolutionary ecology and biogeography - Harshita Bhatia; Purushottam Adhikari; Poonam Verma; Yogesh Pal Singh; Tao Su; Gaurav Srivastava (iScience)
Summary: The evolutionary history of bamboo has remained elusive, primarily due to the scarcity of fossils that exhibit varied morphological traits, often lacking detailed features. In this study, we introduce a remarkable fossil find, a bamboo culm from the early Miocene sediments of the Neyveli lignite mine in India. This fossil is distinguished by its nodal buds and notably ventricose (swollen) nodes—features rarely preserved in the fossil record. This unique specimen stands alone to showcase such specific morphological characteristics and is the earliest known bamboo fossil from southern India. Its discovery is a significant breakthrough in the study of bamboo diversity, offering fresh insights into the morphological evolutionary history of bamboo and lending support to the hypothesis of a Gondwanan origin for Asian bamboos. Furthermore, this fossil is crucial for reconstructing past environments, suggesting that ancient bamboos likely evolved in warm, humid climatic conditions.